Open removal models with temporary emigration and population dynamics to inform invasive animal management. Issue 8 (17th August 2022) - Udell, Bradley; Martin, Julien; Romagosa, Christina; Waddle, Hardin; Johnson, Fred; Falk, Bryan; Yackel Adams, Amy; Funck, Sarah; Ketterlin, Jennifer; Suarez, Eric; Mazzotti, Frank
Abstract: Removal sampling data are the primary source of monitoring information for many populations (e.g., invasive species, fisheries). Population dynamics, temporary emigration, and imperfect detection are common sources of variation in monitoring data and are key parameters for informing management. We developed two open robust‐design removal models for simultaneously modeling population dynamics, temporary emigration, and imperfect detection: a random walk linear trend model (estimable without ancillary information), and a 2‐age class informed population model (InfoPM, closely related to integrated population models) that incorporated prior information for age‐structured vital rates and relative juvenile availability. We applied both models to multiyear, removal trapping time‐series of a large invasive lizard (Argentine black and white tegu, Salvator merianae ) in three management areas of South Florida to evaluate the effectiveness of management programs. Although estimates of the two models were similar, the InfoPMs generally returned more precise estimates, partitioned dynamics into births, deaths, net migration, and provided a decision support tool to predict population dynamics under different effort scenarios while accounting for uncertainty. Trends in tegu superpopulation abundance estimates were increasing in two management areas despite generally high removal rates. However, tegu abundance appeared to decline in the Core management area, where trapping density was the highest and immigration the lowest. Finally, comparing abundance predictions of no‐removal scenarios to those estimated in each management area suggested significant population reductions due to management. These results suggest that local tegu population control via systematic trapping may be feasible with high enough trap density and limited immigration; and highlights the value of these trapping programs. We provided the first estimates of tegu abundance, capture probabilities, and population dynamics, which is critical for effective management. Furthermore, our models are applicable to a wide range of monitoring programs (e.g., carcass recovery or removal point‐counts). Abstract : This work extends removal abundance models to estimate animal abundance while accounting for imperfect detection, availability bias, and population dynamics (both within and between years). We develop two models, one that can be estimated without ancillary information, and a second (an informed population model, InfoPM) that also incorporates information on age‐structured vital rates. We apply these models to estimate the population dynamics (births, survival, migration) of an invasive lizard (Argentine black and white tegus) in three management areas in South Florida.